Stagnation Point Flow over a Stretching Sheet with Convective Boundary Conditions - Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Roslinda, Nazar; Anuar, Ishak (2012)
In this study, the numerical investigation of stagnation point flow over a stretching surface with Newtonian heating and convective boundary conditions are considered. The transformed boundary layer equations are solved numerically using the Keller-box method. Numerical solutions are obtained for the local heat transfer coefficient, the surface temperature as well as the temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, stretching parameter and conjugate parameter are analyzed and discussed. As a conclusion, the thermal boundary layer thickness depends strongly on these three parameters. It is found that, as Prandtl number and stretching parameter increase, the temperature profiles decrease. While, as conjugate parameter decrease, the temperature profiles also decrease.